Overview of Dry Eye Severity in Diabetic Retinopathy Patients - Humaira, Fatihah Annisa; Vitresia, Havriza; Noverial, Noverial (GLOBAL HEALTH SCIENCE GROUP, 2024)
Dry eye is often found in patients with diabetes mellitus. One of the microvascular complications of diabetes mellitus is diabetic retinopathy. Dry eye in diabetic retinopathy patients is caused by chronic hyperglycaemia which causes microvascular and nerve damage resulting in decreased tear secretion and hyperosmolarity and activates inflammatory mediators that can damage conjunctival goblet cells and decrease mucin secretion. Objective: This study aims to determine the description of dry eye severity through the OSDI scoring system and ferning test in diabetic retinopathy patients based on its degree. Method: This study uses a descriptive method with a cross sectional design. The number of samples in the study were 64 people with a diagnosis of diabetic retinopathy. The sampling technique in this study was carried out by consecutive sampling. Result: The study was conducted using the OSDI questionnaire and ferning test examination on samples that had been diagnosed with diabetic retinopathy based on predetermined inclusion and exclusion criteria. The research data were compiled using Microsoft Excel and then reviewed for completeness. Then the complete data was processed using a computer programme, namely the Statistical Package for Social Sciences (SPSS). The results obtained from this research are most patients were female (64.1%), aged 45-65 years (79.7%), diabetes mellitus duration >5 years (60.9%). The most common degree of retinopathy with dry eye was PDR (64.1%). The most common degree of dry eye and type of ferning was severe dry eye (62.5%) and type IV (59.4%) which mostly occurred in patients with PDR. Conclusions: Based on the OSDI score and ferning test in the study conducted on diabetic retinopathy patients based on the degree, all patients had dry eye (100%).